Evaluation of the Effects of Genistein In Vitro as a Chemopreventive Agent for Colorectal Cancer-Strategy to Improve Its Efficiency When Administered Orally (2022)
ABSTRACT: Colorectal Cancer (CRC) ranks third in terms of incidence and second in terms of mortality and prevalence worldwide. In relation to chemotherapy treatment, the most used drug is 5-fluorouracil (5-FU); however, the use of this drug generates various toxic effects at the systemic level. For this reason, new therapeutic strategies are currently being sought that can be used as neoadjuvant or adjuvant treatments. Recent research has shown that natural compounds, such as genistein, have chemotherapeutic and anticancer effects, but the mechanisms of action of genistein and its molecular targets in human colon cells have not been fully elucidated. The results reported in relation to non-malignant cell lines are also unclear, which does not allow evidence of the selectivity that this compound may have. Therefore, in this work, genistein was evaluated in vitro in both cancer cell lines SW480 and SW620 and in the non-malignant cell line HaCaT. The results obtained show that genistein has selectivity for the SW480 and SW620 cell lines. In addition, it inhibits cell viability and has an antiproliferative effect in a dose-dependent manner. Increased production of reactive oxygen species (ROS) was also found, suggesting an association with the cell death process through various mechanisms. Finally, the encapsulation strategy that was proposed made it possible to demonstrate that bacterial nanocellulose (BNC) is capable of protecting genistein from the acidic conditions of gastric fluid and also allows the release of the compound in the colonic fluid. This would allow genistein to act locally in the mucosa of the colon where the first stages of CRC occur.